Relation of Subjective Quality of Life to Motor Symptom Profile in Parkinson's Disease - Erica R. Appleman; Karina Stavitsky; Alice Cronin-Golomb (Parkinson's Disease)
Parkinson's disease (PD) presents with extensive heterogeneity in symptomatology, inviting examination of disease subtypes. One significant categorization is by whether patients present at onset with tremor as the dominant symptom (TD) or with nontremor symptoms (NTD). We examined differences in quality of life between TD and NTD patients using the Parkinson's Disease Questionnaire-39 (PDQ-39), correlating performance with aspects of motor function as indexed by the Unified Parkinson's Disease Rating Scale (UPDRS). Participants included 35 nondemented individuals (19 TD, 16 NTD) matched on clinical and demographic characteristics. NTD had significantly lower overall PDQ-39 scores, particularly for the mobility subscale. Several UPDRS subscale scores significantly correlated with quality of life, especially for NTD. Further, the correlations were driven by nontremor type symptoms, even in TD patients. Determining reliable subtypes of PD may aid in prognosis and treatment optimization, thereby enhancing quality of life in afflicted individuals.